Development of a model for coloring raster elements of polynomial transformation of digital images - Kavyn, Bohdan (Technology audit and production reserves, 2025)
The object of the study is the process of pre-printing image preparation, in particular the final stage of preparing an image for printing – rasterization using polynomial transformation. One of the problems in the process of preparing an image for printing is the lack of a program in computer graphics programs and a raster processor for constructing gradation characteristics and rasterization characteristics. This work used scientific research methods, in particular the method of mathematical modeling, object-oriented programming and the MATLAB:Simulink software package. In the process of the study, rasterization models of polynomial transformation of digital images were built and simulators for simulation modeling were developed. Gradation characteristics, rasterization characteristics and optical density of the raster elements were obtained, which quantitatively and qualitatively describes the raster tone reproduction of printed images. The developed model of coloring for determining the amount of paint on the surface of raster elements of polynomial transformation of images of light tones allows to correct the image based on the analysis of the properties of gradation characteristics, characteristics of screening and optical density in a wide range of tone reproduction. Thanks to the proposed model, the informativeness of the analysis of tone reproduction is significantly expanded. This is a significant advantage over the model based on power transformation, which has limitations in terms of the reproduction of dark tones and causes the phenomenon of posterization. Based on the obtained results of coloring raster elements of typical variants of polynomial transformation for a polynomial thickness value H=1 μm it was established that an increase in the thickness of the paint layer by 20 % of the nominal shifts the initial values of coloring. In particular: at V=1.2 the characteristics shift towards dark tones – the image darkens, and at V=0.8 the characteristics of coloring shift towards midtones – the image becomes lighter. The results of the conducted studies of raster tones can be applied at the stage of preparing digital images for rasterization in computer publishing systems.